THE IMPLEMENTATION OF GENERATE ARGUMENT INSTRUCTION MODEL ON OPTICAL MATERIAL TO IMPROVE STUDENTS ARGUMENTATION SKILLS IN SMP 20 PEKANBARU GRADE VIII - Armila Jayanti; M. Nor; M. Rahmad (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2018)
Scientific argumentation is one of the thinking ability which important to be trained in order to make students not only focus on solving quantitative problem and analyze physics phenomena in daily life. This study was aimed to determine the effect of Generate Argument Instruction model toward student argumentation skills on optical material. Quasy experiment was use as study model by using intact group comparison. The population in this study were students grade VIII of SMPN 20 Pekanbaru which consisted of seven classes. Two classes whas choossen to be experiment and control class based on normality and homogenity test. The data was analyze by using descriptive and inferential statistic techniques. The result of this study showed there was a sifnificant influence toward students argumentation skill between experiment class that using implementy Generate Argument Instructional Model and control class that using conventional learning. The argumentation skill of experimental class was higher than class control (12,7%). It can be conclude, the generate argument instructional model gave the positive effect toward student’s argumentation skills.